OPTIMIZING THE ASSIGNMENT OF KRI AS AN AMMUNITION AUXILIARY SHIP IN AMMUNITION DISTRIBUTION TO SUPPORT THE DUTIES OF THE INDONESIAN NAVY - Adi Wirasmo; Udisubakti Cipto Mulyono; yoyok Nurkarya Santosa; Azi Wardiana (JOURNAL ASRO, 2022)
The distribution of ammunition is not optimal because there is only one Arsenal and must serve Navy Bases spread throughout Indonesia and have been specially transported ammunition so the process of distributing ammunition depends on the element of the title. Selection of the right type of KRI in an assignment as an ammunition auxiliary ship using the Analytic Network Process (ANP) method approach gave rise to two main criteria, namely the criteria of operational requirements with five sub-criteria: safety, geographical conditions, mobility, ship feasibility, sailing resilience, and technical requirements criteria with five sub-criteria: machinery, navigation, platform safety. equipment and also sensors. For ammunition,and distribution errors use the Vehicle Routing Problem method. Route optimization is approached with the Saving Matrix method. The results of this study are an alternative priority for selecting ships in assignments as ammunition auxiliary ships to carry out the distribution of ammunition throughout the Navy Base. The best alternative based on the main criteria and sub-criteria is the type of personnel transport auxiliary ship (BAP) with a score of 0.341260. Sequentially, the alternative priorities in the selection of ammunition auxiliary ships are BAP Type Ships, BRS Type Ships, LST / M Type Ships, AT Type Ships, and the last priority is MA Type Ships. Meanwhile, the Saving Matrix method is able to improve the ammunition distribution route into two routes so as to reduce distribution operational costs. The use of the Nearest Insert and Nearest Neighbor methods was able to shorten the distance traveled by the ship from 13004 Nm to 9667 Nm. Keywords: Analytic Network Process (ANP), Vehicle Routing Problem (VRP), Saving Matrix, Nearest Insert, Nearest Neighbor